2001
DOI: 10.1016/s0550-3213(01)00066-9
|View full text |Cite
|
Sign up to set email alerts
|

QCD3 and the replica method

Abstract: Using the replica method, we analyze the mass dependence of the QCD 3 partition function in a parameter range where the leading contribution is from the zero momentum Goldstone fields. Three complementary approaches are considered in this article. First, we derive exact relations between the QCD 3 partition function and the QCD 4 partition function continued to half-integer topological charge. The replica limit of these formulas results in exact relations between the corresponding microscopic spectral densitie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 55 publications
3
75
0
Order By: Relevance
“…The formulas (5.25), (5.26) which we obtained in the proof of Theorem 1.1 for t < 0, hold also in the case t > 0, if we replace Ψ (1) by Ψ (2) . We obtain from (3.11) and condition d) in the RH problem for Ψ + that as z → √ t,…”
Section: Small Norm Rh Problemmentioning
confidence: 67%
“…The formulas (5.25), (5.26) which we obtained in the proof of Theorem 1.1 for t < 0, hold also in the case t > 0, if we replace Ψ (1) by Ψ (2) . We obtain from (3.11) and condition d) in the RH problem for Ψ + that as z → √ t,…”
Section: Small Norm Rh Problemmentioning
confidence: 67%
“…It has long been known [2][3][4][5][6][7][8][9][10][11][12] that this is the case for perturbative calculations such as for the expansion of the resolvent in an asymptotic series in 1/x. Problems are known to occur when one attempts to derive exact nonperturbative results for the quenched average resolvent [4,7].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that bosonic and fermionic replica limits lead to different results for the two point function of the Gaussian unitary ensemble and that neither limits lead to the correct result [4]. The original critique [4] motivated an insightful and challenging debate [5][6][7][8][9][10][23][24][25]] the details of which have been accounted for in the introduction of [26]. The debate lead to the generally accepted belief that, although the replica trick correctly reproduces the asymptotic expansion of the microscopic spectral correlation functions, it can not be trusted for nonperturbative calculations except in a few cases, when the series can be resummed [24] or simply terminates [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…(For the application of Virasoro constraints on the effective finite volume partition function see, for example, Refs. [33][34][35]). …”
Section: Introductionmentioning
confidence: 99%